A SURVEY FOR STUDENTS’ EXPERIENCE IN SMALL GROUP LEARNING CLASSROOM OF HISTOLOGY - Milenkova, Liljana; Kakasheva, Lena Mazhenkovska; Petrova, Irena Kostadinova; Gerasimovska, Zorka; Kostovski, Marko (Journal of Morphological Sciences; Vol 2 No 1 (2019): JMS, 2019)
Small group learning during practical sessions of histology & embryology was adopted to overcome students’  ‘authority-dependence’ and to enable creative thinking and learning in a socially cohesive group, for enhancing the learning process and developing certain skills. The study aims to identify students’ perception of the usefulness (in general) as well as of certain advantages of the learning process and gaining self-confidence. Online survey consisting of 13 questions/statements the students are supposed to give opinion on, by stating degree of agreement. Results are based on a four grade Likert type scale of evaluation. About half of the students practicing small group learning for the first time, expressed a strongly positive opinion in the survey. They find this method of cooperative learning favorable for: enhancement of the learning process, rational organization of time, conclusion drawing, learning how to apply knowledge in practice, rising motivation. Over all, students practicing small group learning for the first time find the cooperative learning very useful. They elucidate its positive effect on time organization and rationalization of the learning process and knowledge applying. The findings are encouraging and motivating for our continuous work with small group learning. They also highlight the need of working on improvement and creating additional ways to promote students’ participation - especially in questioning, answering and statement elaborating. This project has got ethical approval from the Committee for ethical research with humans. The survey which is part of the project was performed with the understanding and consent of the students. Key words: Small group learning, students’ perception, survey,